2015
DOI: 10.1002/ajmg.a.37155
|View full text |Cite
|
Sign up to set email alerts
|

Copy number variants including RAS pathway genes—How much RASopathy is in the phenotype?

Abstract: The RASopathies comprise a group of clinically overlapping developmental syndromes the common pathogenetic basis of which is dysregulated signal flow through the RAS-MAPK pathway. Mutations in several components or modifiers of the pathway have been identified in Noonan syndrome and related disorders. Over the past years copy number variants (CNVs) encompassing RAS pathway genes (PTPN11, RAF1, MEK2, or SHOC2) have been reported in children with developmental syndromes. These observations raised speculations th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…In each of these cases, gene duplication is thought to result in increased dosage of SHP2 which has the equivalent effect as the common gain of function mutation in PTPN11 associated with NS. In addition, rare chromosomal duplications associated with SHOC2 in a NS patient [56], and RAF1 and MAP2K2 in patients with mild RASopathy spectrum phenotypes have been reported [57, 58]. Chromosomal deletions have also been reported to be associated with a RASopathy phenotype.…”
Section: Copy Number Variation Associated With Rasopathy Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…In each of these cases, gene duplication is thought to result in increased dosage of SHP2 which has the equivalent effect as the common gain of function mutation in PTPN11 associated with NS. In addition, rare chromosomal duplications associated with SHOC2 in a NS patient [56], and RAF1 and MAP2K2 in patients with mild RASopathy spectrum phenotypes have been reported [57, 58]. Chromosomal deletions have also been reported to be associated with a RASopathy phenotype.…”
Section: Copy Number Variation Associated With Rasopathy Genesmentioning
confidence: 99%
“…Chromosomal deletions have also been reported to be associated with a RASopathy phenotype. A chromosomal deletion encompassing the BRAF locus at 7q34 was reported in two individuals with phenotypes overlapping several RASopathies [58, 59]. In addition, two studies reported interstitial deletion of 19p13.3 encompassing the MEK2 gene [60, 61].…”
Section: Copy Number Variation Associated With Rasopathy Genesmentioning
confidence: 99%
“…g ., pancreatic cancer [16]) and developmental disorders, including Noonan syndrome [17,18,19]. Whereas the latter is thought to be commonly caused by dysregulation of mainly one pathway, the RAS-MAPK pathway [19], RAS-mediated cancer progression involves activation of several pathways, e . g ., PI3K-AKT [3,20], RALGDS-RAL [9,13], PLCε-second messengers [14] or Hippo-YAP [21] as well as RAS-MAPK [22].…”
Section: Introductionmentioning
confidence: 99%
“…Lissewski et al [] took on the difficult task of arguing the absence of the variable Noonan syndrome or rasopathy phenotype in individuals with a copy number variation (CNV) affecting RAS/MAPK pathway genes. This is an important report because it challenges the assumption that gene duplication results in similar phenotypic findings as missense mutations associated with a gain‐of‐function of the abnormal protein product.…”
mentioning
confidence: 99%
“…While Lissewski et al [] report on individuals with CNVs encompassing genes of the RAS/MAPK pathway, their message is relevant for other genetic disorders. In contrast to loss‐of‐function mutations acting through haploinsufficiency for the functional gene product, in which a whole gene deletion has the same effect as a nonsense mutation, it is not possible to conclude that a gene duplication has an effect comparable to constitutive activation of a gene product.…”
mentioning
confidence: 99%